(untitled) (The International Journal of Educational Sciences and Arts, 2024)
Gamification is one of the effective tools in influencing students’ learning experiences and learning outcomes, which has a positive impact on the student’s psychological health and emotional well-being. Since emotional intelligence and its variables are one of the requirements for learning English for students in general education stages, examining the mechanisms of the impact of gamification on emotional intelligence is a research priority. Accordingly, the current research came to study the experts’ point of view on the uses of gamification to enhance emotional intelligence among general education students studying English as a foreign language. The current research relied on the phenomenological approach based on semi-structured interviews with (6) English language teachers who use gamification tools the most in educational settings. According to the objective analysis processes, the results of the study, as expressed by specialized education experts, reached that the uses of gamification in enhancing emotional intelligence among English language students contributed to enhancing essential emotional skills in emotional intelligence such as: motivation, self-regulation, social skills, and empathy. In contrast, they described to us some of the challenges they face while using gamification, such as: variation in emotional intelligence among students, loss of emotional feeling, anxiety and stress. Therefore, the study recommended the importance of continuing research related to emotional intelligence, educational games and gamification, and applying various measurement tools in this field. As well as working on increasing educational games related to the objectives of the curriculum.